A review of radio frequency identification technology for the anatomic pathology or biorepository laboratory: Much promise, some progress, and more work needed - Jerry J Lou; Gary Andrechak; Michael Riben; William H Yong (Journal of Pathology Informatics, 2011)
Patient safety initiatives throughout the anatomic laboratory and in biorepository laboratories have mandated increasing emphasis on the need for accurately identifying and tracking biospecimen assets throughout their production lifecycle and for archiving/retrieval purposes. However, increasing production volume along with complex workflow characteristics, reliance on manual production processes, and required asset movement to disparate destinations throughout asset lifecycles continue to challenge laboratory efforts. Radio Frequency Identification (RFID) technology, use of radio waves to communicate data between electronic tags attached to objects and a reader, shows significant potential to facilitate and overcome these hurdles. Advantages over traditional barcode labeling include readability without direct line-of-sight alignment to the reader, ability to read multiple tags simultaneously, higher data storage capacity, faster data transmission rate, and capacity to perform multiple read-writes of data to the tag. Most importantly, use of radio waves decreases the need to manually scan each asset, and at each step, identification or tracking event is needed. Temperature monitoring by on-board sensors and three-dimensional position tracking are additional potential benefits of using RFID technology. To date, barriers to implementation of RFID systems in the anatomic laboratory include increased associated costs of tags and readers, system software, data security concerns, lack of specific data standards for stored information, and potential for technological obsolescence during decades of specimen storage. Novel RFID production techniques and increased production capacity are projected to lower costs of some tags to a few cents each. Potentially, information security concerns can be addressed by techniques such as shielding, data encryption, and tag pseudonyms. Commitment by stakeholder groups to develop RFID tag data standards for anatomic pathology and biorepository laboratories could avoid or mitigate the "islands of data" dilemma presented by barcode usage where there are innumerable standards and a consequent paucity of hardware or software "plug and play" interoperability. Work remains to be done to establish the durability and appropriate shielding of individual tag types for use in harsh laboratory environmental conditions, and for long-term archival storage. Finally, given the requirements for long-term storage of biospecimen assets, consideration should be given to ways of mitigating data isolation due to eventual technological obsolescence of a particular RFID technology or software.